Small Farm Food Safety, Fresh Produce: Additional Resources for Participants Bringing Food Safety Concepts to Farms - Brian Lapinski; Amy Simonne; Marilyn E. Swisher (EDIS)
FCS-8850, a 2-page fact sheet by Brian Lapinski, Amy Simonne, and M.E. Swisher, is a bibliography listing online resources providing general information on produce safety, commodity-specific food safety guidelines, and consumer information. Published by the UF Department of Family Youth and Community Sciences, October 2007.